2006
DOI: 10.4103/1319-3767.27740
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori seropositivity in children with chronic disease in Jeddah, Saudi Arabia

Abstract: Infection with H. pylori seems to occur early in life and its prevalence increased with age in Jeddah, Saudi Arabia. The risk of H. pylori infection was significantly increased within children suffering from chronic hemolytic anemia; neurological impairment compared to controls and was significantly related to severity of the chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
1
17
2
Order By: Relevance
“…Host iron is known to be essential for pathogen growth [17]. However, there have been inconsistent reports on the roles of iron in the acquisition of H. pylori infection [17][18][19]. Perhaps, the iron overload in thalassemia patients might have contributed to the high prevalence of H. pylori infection observed in our study.…”
Section: Resultscontrasting
confidence: 39%
“…Host iron is known to be essential for pathogen growth [17]. However, there have been inconsistent reports on the roles of iron in the acquisition of H. pylori infection [17][18][19]. Perhaps, the iron overload in thalassemia patients might have contributed to the high prevalence of H. pylori infection observed in our study.…”
Section: Resultscontrasting
confidence: 39%
“…In the remaining seventeen studies, two reviews 14, 21 and eight publications not being case-control design 22-29 were discarded. Then, a total of seven case-control studies were identified, of which two studies not presenting detailed raw data were further excluded 30, 31. Finally, five case-control studies were included in this study 32-36.…”
Section: Resultsmentioning
confidence: 99%
“…In a different study the same authors found that colo- In Jeddah, Saudi Arabia, 1432 children; were tested for H. pylori status by ELISA using IgG antibodies (HM-CAP; Enteric Products Incorporation, Westbury, NY). The prevalence did not differ according to nationality and gender but significantly increased with age in children with chronic asthma, chronic anemia and neurological impairment (P < 0.01 for all), length of illness, number of blood transfusions, number of hospital admission and type of feeding (14).…”
Section: Discussionmentioning
confidence: 95%